Exploitation of biotic inducers and hyperparasites as potential biological control against foliar diseases in peanut : Exploitation of biotic inducers and hyperparasites as potential biological control against foliar diseases in peanut - DURGADEVI; D L RAJENDRAN; G KARTHIKEYAN; T RAGUCHANDER (Journal of Oilseeds Research, 2023)
Field experiments were conducted to study the efficacy of biotic inducers namely salicylic acid (SA), methyl jasmonate (MeJA) and Beta amino barbutric acid (BABA) and Plant growth promoting microbes viz., Trichoderma asperllum and Bacillus subtilis, hyperparasite (Spharellopsis filum) along with fungicide (carbendazim) against foliar diseases of groundnut. In the study, vacuum seed infiltration application along with foliar spray of biotic inducers @ 30, 45 and 60 days after planting significantly reduced the late leaf spot (23.8) while S. filum recorded least rust incidence (11.21) and also increased the pod yield compared to fungicide and untreated control. The induced defense enzymes namely phenol (46 μg of catechol / g of fresh tissue) and Phenyl alanine ammonia lyase (1.754nmol/min/g) was also high in biotic inducers and S. filum treated plants followed by B. subtilis treated peanut plants.